(untitled) (Global Journal of Management and Business Research, 2019)
This paper aims to investigate the effect of electronic-word-of-mouth (e-WOM) on brand awareness and equity for the emerging segment of sunset restaurants. By applying the method of user-generated content analysis the current research examines the impact of reviews posted on TripAdvisor regarding sunset restaurants in Thailand. The findings of the study indicate that certain contextual elements along with content characteristics enhanced the brand relationships between the travelers and dining establishments. The meta-commentary interpretation of the online content reveals that recommendation reciprocity and review consensus stimulate the affinity among the users while increasing the visitor empathy for particular restaurants.